THE PHENOMENON OF CONFLICT IN EDUCATION FOR SECURITY ON THE EXAMPLE OF THE CZECH REPUBLIC (PART I) - Janusz Mika (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2016)
Security belongs to the basic qualitative standards of citizens´ life in every country. It is a very frequently discussed question involving education for security. The paper presents a concise analysis of the phenomenon related to the conflict of education for security using the example of the Czech Republic.